Morphosyntactic interference from quechua to spanish: a study in Jangas district, Ancash - Valverde Chávez, Cecilia de las Nieves (2019)
The Andean Spanish spoken in Jangas is a dialect variety resulting from language contact between the standard Spanish of Peru and the quechua spoken in Jangas, district of the province of Huaraz in the department of Ancash. This contact of languages generates different types of linguistics interferences, such as phonic, morphological, syntactic and lexical interference. The purpose of this article is analyze the morphosyntactic interferences from the source language (quechua) to the target language (Spanish) in speakers from Jangas. The data obtained in the development of this research show as a result phenomena such as linguistic omission, grammatical disagreement, linguistic insertion, anomalous pronouns, dequeism, etc. Finally, it is concluded that the phenomenon with greater markedness is that of grammatical disagreement, this may be the product of this phenomenon being the most common in language contact situations.